The Combined Dexamethasone/TSST Paradigm – A New Method for Psychoneuroendocrinology - Andrews, Julie; D’Aguiar, Catherine; Pruessner, Jens C. (PLOS ONE, 2012)
The two main physiological systems involved in the regulation of the stress response are the hypothalamus-pituitary-adrenal (HPA) axis and the sympathetic nervous system (SNS). However, the interaction of these systems on the stress response remains poorly understood. To better understand the cross-regulatory effects of the different systems involved in stress regulation, we developed a new stress paradigm that keeps the activity of the HPA constant when exposing subjects to psychosocial stress. Thirty healthy male participants were recruited and randomly assigned to either a dexamethasone (DEX; n = 15) or placebo (PLC; n = 15) group. All subjects were instructed to take the Dexamethasone (2 mg) or Placebo pill the night before coming to the laboratory to undergo the Trier Social Stress Task (TSST). Salivary cortisol, salivary alpha amylase (sAA), heart rate, blood pressure and subjective stress were assessed throughout the protocol. As expected, the DEX group presented with suppressed cortisol levels. In comparison, their heart rate was elevated by approximately ten base points compared to the PLC group, with increases throughout the protocol and during the TSST. Neither sAA, nor systolic or diastolic blood pressures showed significant group differences. Subjective stress levels significantly increased from baseline, and were found to be higher before and after the TSST after DEX compared to placebo. These results demonstrate a significant interaction between the HPA and the SNS during acute stress. The SNS activity was found to be elevated in the presence of a suppressed HPA axis, with some further effects on subjective levels of stress. The method to suppress the HPA prior to inducing stress was found to completely reliable, without any adverse side effects. Therefore, we propose this paradigm as a new method to investigate the interaction of the two major stress systems in the regulation of the stress response.